2019
DOI: 10.4038/jas.v14i2.8512
|View full text |Cite
|
Sign up to set email alerts
|

Willingness to Pay for Fruit Attributes: A Conjoint Analysis

Abstract: Purpose: Identification of consumer preferences is important in designing products. Producers will immensely benefit by knowing them to capture the market share. In light of this, we evaluate consumers' stated preferences for various attributes of four popular fruits: grapes, sweet orange, pear and pomegranate. Research Method: We run a Rank Ordered Logistic Regression (ROLOGIT) and calculate Willingness to Pay (WTP) for fruit attributes. Findings: We find that the perception of the fruits selected is continge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…Finally, as expected, we found that price plays a fundamental role at the time of purchase: in particular, for each class except for the first, the price has a negative and significant effect, which indicates that the propensity to purchase decreases when the price increases. These results agree with what reported by Ranasingha et al (2019), who, by conducting a CE on pomegranates and other fruits, found that price is always inversely proportional to the purchasing choice. Recently, Darko et al (2013) and Christensen et al (2019) reported that price can be considered a barrier to buying F&V, especially for low-income categories.…”
Section: Discussionsupporting
confidence: 92%
“…Finally, as expected, we found that price plays a fundamental role at the time of purchase: in particular, for each class except for the first, the price has a negative and significant effect, which indicates that the propensity to purchase decreases when the price increases. These results agree with what reported by Ranasingha et al (2019), who, by conducting a CE on pomegranates and other fruits, found that price is always inversely proportional to the purchasing choice. Recently, Darko et al (2013) and Christensen et al (2019) reported that price can be considered a barrier to buying F&V, especially for low-income categories.…”
Section: Discussionsupporting
confidence: 92%
“…Along with the issues mentioned above, crop quality is critical for the economic value of tree and vine crops along with yield (Fereres and Evans 2006). Factors affecting crop price include fruit size (Lötze and Bergh 2004), color (Ranasingha et al 2019), uniformity (Calderon-Orellana et al 2014, sugar content (brix) (Kajikawa 1998), flavor and firmness (Marsal et al 2010;Diehl et al 2015), and others. While these factors can vary in importance depending upon the specific crop (Diehl et al 2015), they share major commonalities across most crops.…”
Section: Introductionmentioning
confidence: 99%
“…The prohibitive cost of fruit makes consumers hesitate to buy it (Nicklas et al, 2017). Similarly, Sri Lankan consumers consider the price of pears more important than sensory attributes such as size, peel color, and shape (Ranasingha et al, 2019). The price of fruit also has a significant influence on consumer satisfaction and behavioral intention (Gao et al, 2014;Kathuria and Singh, 2016;Nasir et al, 2017).…”
Section: Fruit Choice Criteriamentioning
confidence: 99%